SIMULASI PELIMPAHAN BEBAN PMT OUTGOING PWI 06 SAAT TERJADI OVERLOAD SHEDDING PADA TRAFO INCOMING 03 GARDU INDUK PURWODADI DENGAN MONITORING VT SCADA BERBASIS ARDUINO MEGA 2560 - Rizkifadhla, Reza; Winarno, Heru (Vocational School Diponegoro University, 2019)
Reza Rizkifadhla, Heru Winarno, in this article explains that overload shedding in incoming transformer occurs due to an increase in load current that exceeds the capacity of the transformer. If overload shedding is not handled, it will cause damage to the transformer, and even cause incoming trip feeders and a very wide blackout effect. Relay overload shedding mounted on incoming feeders works to anticipate overload shedding by deliberately releasing outgoing feeders gradually to reduce the load. This study aims to provide a simulation of the conditions of incoming feeders during normal times, during overload shedding and handling of outgoing feeders deliberately released by carrying out load maneuvers to other feeders with different incoming transformers. Maneuvers are carried out to maintain the reliability of the continuity of electricity distribution. In this study one simulation tool was designed. The design of this tool uses a relay and Arduino Mega 2560 as a control center. Arduino Mega 2560 reads the current using the ZMCT 103C sensor. The simulation is based on the overload shedding event that has occurred in Purwodadi Substation. As for controlling switching equipment and monitoring current and voltage is done using HMI with VT Scada software. In the experiment, 3 incoming normal currents were 2.2 A with a load of 5 12 VAC 5W lamps. Simulated maneuvering error, the load on incoming 3 increased to 2.60 A. This situation is considered to have reached the condition of overload shedding, relay PMT C trip to reduce the load. Incoming 3 returns back to normal, namely 1.68 A. Loads on PMT C that are extinguished are maneuvered to PMT E or PMT F which have different incoming.